The efficacy of modified flapless corticotomy using piezocision procedure to accelerate orthodontic tooth movement in premolar extraction cases - Sultana, Sharmin (2021)
This study aimed to investigate the efficacy of modified piezocision procedure to accelerate the levelling and alignment stage in orthodontic treatment with first premolar extraction cases of the maxilla and mandible and evaluate its effects on the gingival recession, periodontal pocket depth, tooth vitality, pain, and satisfaction score. The sample comprised 16 patients with Little’s Irregularity Index (LII) between 7-9 mm in the maxillary and mandibular incisors and require extraction of first premolars for both jaws. The subjects were randomly allocated into the control group, and the piezocision group and the recruited subjects were divided into two parallel groups with a 1:1 allocation ratio. Both groups received McLaughlin Bennett Trevisi (MBT) prescription brackets of the 0.022-inch slot. The experimental group received piezocision surgery on the same bonding day. Maxilla and mandibular study cast were taken at a monthly interval to assess the overall alignment time, changes in the LII, and alignment rate. The periodontal parameters (gingival recession and pocket depth) and pulp vitality test were evaluated. Patient perception of the pain level and level of satisfaction with a numeric rating scale was assessed following the piezocision procedure. A total of 13 patients (7 control and 6 piezocision) in the maxilla completed the study, whereas, in the mandible, a total of 10 patients (7 control and 3 piezocision) completed the study. The overall treatment time to complete the levelling and alignment was significantly shorter in the piezocision group compared to the control group in the maxilla (mean difference = 31.5, 95% CI: 6.5, 56.5; P = 0.018), whereas, in the mandible, the result was non-significant. In the maxilla, changes of LII had significantly reduced at the second month and alignment rates were significantly faster in the first two months in the piezocision group compared to the control group, but no significant difference in the mandible. Gingival recession, pocket depth, and pulp vitality of the maxillary and the mandibular teeth remained stable in both groups throughout the observation period of this study. Patients had reported a mild to no pain score and a satisfactory score about the piezocision procedure. Piezocision seems to be an effective method to decrease the overall levelling and alignment time and accelerating orthodontic tooth movement. However, the significant efficacy was found only in the maxilla and convincing efficacy to the mandible. The piezocision procedure did not produce any adverse effects on periodontal structure and vitality on the tooth; also, it seems a less painful and satisfactory surgical approach.